Nonprofit fundraising 101 - Heyman, Darian Rodriguez (Wiley, 2015)
Raise more money for your cause! Based on expert advice and insights from a variety of respected industry experts, Nonprofit Fundraising 101 is an essential text for nonprofit professionals, volunteers, activists, and social entrepreneurs who want to leverage best practices to promote their cause. Built upon the success of the best-selling Nonprofit Management 101, this easy to digest book provides practical, comprehensive guidance for nonprofit fundraising around the globe. With tips and tools, expert advice, and real-world insights from almost fifty industry leaders, this robust resource addresses the entire spectrum of fundraising for nonprofits, including: -Planning, hiring, and tracking progress -Individual donors, major gifts, events, and direct mail -Board and volunteer engagement -Foundation and government grants -Corporate partnerships -Online and email fundraising -Social media and mobile crowdfunding -Earned income and social enterprise Written by and for front line practitioners and geared towards a global audience of emerging and established leaders, this field guide offers step-by-step formulas for success. Nonprofit Fundraising 101 features a foreword by fundraising guru and Soul of Money author Lynne Twist, insights from notable non-profit professionals such as CNN's Van Jones, and an afterword by Kiva.org Co-Founder & President Premal Shah. This book also provides indispensible ideas and diverse case studies ranging from grassroots efforts to the ALS Ice Bucket Challenge, and advice for organizations of all sizes and focus. Chapters are brief and easily digestible, featuring extensive resources for additional learning, concrete best practices, and pitfalls to avoid. Enjoy this must-read manual to learn tried and true ways to raise more money for your cause, nonprofit, or charity.